Small hepatocellular carcinomas displayed as a ring enhancing mass on arterial phase MRI in the chronically diseased liver. Issue 11 (November 2017) - Jones, R.H.; Taylor, A.J.; Rostambeigi, N.; Spilseth, B.
Abstract : Aim: To assess the prevalence of arterial phase (AP) ring-enhancing small hepatocellular carcinomas (HCC) on magnetic resonance imaging (MRI); detail additional MRI features that enable HCC diagnosis; and examine arterial timing as one possible cause of this appearance. Materials and methods: Patients undergoing HCC screening with both computed tomography (CT) and MRI within 40 days were examined at a single institution over a 7- year time period ending in 2013. From this initial group, small (1–3 cm), (AP) ring-enhancing HCC on MRI were studied. Results: From the initial group of 64 patients with 129 HCC, 20 patients with 78 HCCs had a small diameter with 32 (41%) having an AP ring at MRI. The mean age of this latter group was 63-years old, with the average tumour diameter of 1.9 cm. Histopathology and secondary imaging supported a diagnosis of HCC in 20 (100%) patients and 31 (97%) lesions. Most of the ringed lesions had early AP timing. Conclusion: This study revealed a high prevalence (41%) of small, AP ring HCC with MRI. The use of other MRI sequences adds support in making the proper diagnosis with this appearance. Early AP timing may help create this pattern. Highlights: Small HCC's (1-3 cm) on contrast enhanced MRI may not only be displayed as a homogeneously enhanced mass in the arterial phase in dynamic imaging, but may have a ringed appearance. These small HCC's need to be distinguished from other arterial ringed masses in the cirrhotic liver such as the hemangioma, intrahepatic cholangiocarcinoma, or a previously treated HCC. Reviewing the subsequent enhancement changes in the remainder of the dynamic sequences and correlating the mass appearance in the other sequences of the exam can be very helpful in separating the arterial ringed HCC from the other arterial ringed lesions in the cirrhotic liver. The cause of the HCC ringed appearance may in part be related to earlier imaging in the arterial phase.